Desain Sistemik untuk Inisiatif Fesyen Melingkar Kolaboratif: Studi Kasus di Surabaya - Handayani, Rahayu Budhi; Piliang, Yasraf Amir (Jurnal Desain Indonesia., 2024)
The environmental and social issues raised by the linear fashion industry are addressed through circular fashion. It utilizes a closed-loop method that encourages mindful behavior along the entire fashion value chain, from creation to disposal. This article describes the application of a systemic design approach to collaborative circular fashion initiatives with a focus on creating sustainable partnerships and promoting circular fashion initiatives between fashion design Universitas Ciputra, the Surabaya city government Environmental Office, and representatives of 40 Kampung Zero Waste. The methodology used in this research study was based on a systemic design approach, which recognized the interconnection and interdependencies within the circular fashion system. Although the research study did not specifically assess the program's impacts it was a crucial first step in creating awareness and initiating collaborative efforts to promote the adoption of circular fashion in Indonesia. Focusing on the early stages of fostering circular fashion with the help of the Surabaya City Government Environmental Office and zero-waste communities produced insightful findings. Future projects and interventions could be built upon a strong foundation that was provided by the systemic design approach and interdisciplinary collaboration. The research results advance knowledge of comprehensive models and collaborative strategies for encouraging circularity in the fashion industry.